Plastic and Reconstructive Surgery Experimental Models and Research Designs - Siemionow, Maria Z. (Springer London : Imprint: Springer, 2015)
With novel approaches to the application of new technologies via research based studies on stem cells, tissue engineering and new fields of reconstructive transplant (face, hand or larynx transplants), this book facilitates access to this latest knowledge which is not traditionally part of the plastic surgery curriculum. Plastic and Reconstructive Surgery - Experimental Models and Research Designs presents pertinent introductions to different fields (stem cell, transplantation, nerve regeneration, tissue engineering) and experimental models which can be used as a tool to develop technologies of interest by various groups of surgeons.   Plastic and Reconstructive Surgery - Experimental Models and Research Designs benefits a range of surgeons, including plastic and reconstructive surgeons, microsurgeons, hand surgeons, orthopedic surgeons, neurosurgeons and transplant surgeons.